Gestão da manutenção para melhoria do sistema produtivo em uma indústria farmoquímica - Silva, Bruno Henrique da (2021)
This work presents key performance indicators of maintenance management in a pharmaceutical industry. The study was based on real industry data, through which indicators such as Mean Time to Repair (MTTR) and Mean Time Between Failures (MTBF) were generated, with the help of the Maintenance Planning and Control (PCM) team aiming at Maximum Availability of assets and possible actions to reduce the number of equipment failures. It brings as a result the availability of assets, production reliability and increases the company's profitability by reducing the cost of out-of-stock.